Inaccurate, inadequate and inconsistent: A content analysis of burn first aid information online. Issue 8 (December 2016) - Burgess, J.D.; Cameron, C.M.; Cuttle, L.; Tyack, Z.; Kimble, R.M.
Highlights: Burn first aid information on the Internet is often inaccurate and inconsistent. Quality and accuracy of information differs based on a website's geographic origin. Agreement between burn agencies and associations on first aid is needed. The public need consistent messages about correct burn first aid information. Abstract: Objective: With the popularity of the Internet as a primary source of health-related information, the aim of this website content analysis was to assess the accuracy and quality of burn first aid information available on the Internet. Methods: Using the search term 'burn first aid' in four popular search engines, the first 10 websites from each search engine were recorded. From a total of 40 websites recorded, 14 websites were evaluated after removing duplicates. Websites were assessed on content accuracy by four independent reviewers with checks conducted on inter-rater reliability. Website quality was recorded based on Health on the Net Code of Conduct (HONcode) principles. Results: Country of origin for the 14 websites was the US (7), Australia (6), and New Zealand (1). The mean content accuracy score was 5.6 out of 10. The mean website quality score was 6.6 out of 12. Australasian websites scored lower for quality but higher for accuracy. The US websites scored higher for quality than accuracy. Website usability and accuracy in a crisis situation were also assessed. The median crisis usability score was 3 out of five, and the median crisis accuracy score was 3.5 out of five. Conclusions: The inaccurate and inconsistent burn first aid treatments that appear online are reflected in the often-incorrect burn first aid treatments seen in patients attending emergency departments. Global consistency in burn first aid information is needed to avoid confusion by members of the public.